Sosialisasi SIUP Usaha Pembesaran Ikan Lele Dumbo di POKDAKAN Oi Cere Kabupaten Bima - Nurul Fatimah Yunita; Beryaldi Agam; Sangkala (PPPM POLITEKNIK NEGERI SAMBAS, 2022)
A Fisheries Business License (SIUP) is a mandatory thing that must be owned by fish farming entrepreneurs to have a license to do business and use the fish cultivation production facilities contained in the letter. It is important for every cultivator to know the procedures for obtaining a SIUP so that the business carried out can run well. The problem found is that most farmers do not have a SIUP because they do not know the purpose and benefits of SIUP for the catfish business they are engaged in. The purpose of this community service is to provide knowledge about doing catfish farming businesses that have SIUP. This service was carried out on September 4-5, 2021 at the Pokdakan OI Cere Nggembe Village, Bolo District, Bima Regency using the socialization method and FGD to the OI Cere Pokdakan which consists of 10 members. The result of the service is that the participants have known the procedures for the SIUP application process and the benefits of having a SIUP in running a dumbo catfish farming business.